2021
DOI: 10.17152/gefad.836544
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Okuma Alışkanlığı ve Problem Çözme Becerisinin İncelenmesi

Abstract: Araştırma sonucunda ortaokula devam eden kız ve erkek öğrencilerin okuma alışkanlıkları ve problem çözme becerilerinin ortalamaları arasında istatistiksel olarak anlamlı farklılık bulunmamaktadır. Ortaokul öğrencilerinin kitap okuma alışkanlığı ve problem çözme becerisi arasında pozitif yönlü bir ilişki olduğu bulunmuştur. Sınıf seviyelerinde okuma alışkanlığı ve problem çözme becerisi ortalamaları istatistiksel olarak anlamlı düzeyde bir fark oluşturmaktadır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…It was stated that gender had no effect on problem solving skills and being male or female did not affect the level of problem solving skills. Similarly, the findings obtained from the study of Sevgi and Karakaya (2021) stated that gender did not affect problem solving skills and did not show a statistical difference. In the light of these findings, it can be concluded that the findings obtained are similar to the findings obtained from other studies in the field and that gender has no effect on problem solving skills.…”
Section: Conclusion and Discussionmentioning
confidence: 59%
“…It was stated that gender had no effect on problem solving skills and being male or female did not affect the level of problem solving skills. Similarly, the findings obtained from the study of Sevgi and Karakaya (2021) stated that gender did not affect problem solving skills and did not show a statistical difference. In the light of these findings, it can be concluded that the findings obtained are similar to the findings obtained from other studies in the field and that gender has no effect on problem solving skills.…”
Section: Conclusion and Discussionmentioning
confidence: 59%
“…Bu nedenle anket sorularında okumaya ayrılan zaman ve okuma sıklığı dışında basılı ve çevrim içi okumayı tercih etme ile ilgili sorulara da yer verilerek yeni bir okuma çerçevesi geliştirilmiştir (OECD, 2019a). Çeşitli çalışmalarda okuma alışkanlığının okuduğunu anlama (Locher & Pfost, 2020;Sartika ve diğerleri, 2020;Suhana & Haryudin, 2017), okuma başarısı (Dökmen, 1994;Leppanen ve diğerleri, 2005;Mcgeown ve diğerleri, 2015), akademik başarı (Akın, 2016;Aksoy, 2017;Berkant & Tüzer, 2017;Cherian & Thomas, 1995;Gallik, 1999;Yılmaz, 2012;Güney ve diğerleri, 2014), okuma öz-yeterliği (Karakoç Öztürk, 2015Uyar Aydın & Balkan, 2022), yazma becerisinin çeşitli yönleri (Akın, 2016;Eminoğlu & Özkan, 2019;Dölek, 2021), beyindeki beyaz cevherin gelişimi (Takeuchi ve diğerleri, 2016), sözcük dağarcığı zenginliği (Santric ve diğerleri, 2019) ve problem çözme becerileri (Sevgi & Karakaya, 2021) ile pozitif yönde ilişkili olduğu ortaya konmuştur.…”
Section: Okumaya Yönelik Motivasyon Kaynakları Ve öğRetmen Desteğiunclassified
“…In the relevant literature, there are many studies illustrating that reading habits were positively related to reading comprehension (Suhana & Haryudin, 2017;Locher & Pfost, 2020;Sartika et al, 2020), reading success (Dökmen, 1994;Leppanen et al, 2005;Mcgeown et al, 2015), academic success (Cherian & Thomas, 1995;Gallik, 1999;Yılmaz, 2012;Güney et al, 2014;Akın, 2016;Aksoy, 2017;Berkant & Tüzer, 2017), reading self-efficacy (Karakoç Öztürk, 2015;Uyar Aydın & Balkan, 2022), various aspects of writing skills (Akın, 2016;Eminoğlu & Özkan, 2019;Dölek, 2021), development of white matter in the brain (Takeuchi et al, 2016), vocabulary depth (Santric et al, 2019 and problemsolving skills (Sevgi & Karakaya, 2021).…”
Section: Motivation Sources For Reading and Teacher Supportmentioning
confidence: 99%
“…Bu yönüyle, okuma alışkanlığı kişiye yaşamı boyunca kullanacağı öğrenme kaynaklarının kapılarını aralamaktadır. Okuma alışkanlığının edinilmesi, birçok entelektüel maharetin de aktif kullanımını sağlamaktadır" (Sevgi ve Karakaya, 2021: 1205.…”
Section: Introductionunclassified